CONCORDANCIA ENTRE LAS PRUEBAS DE HEMAGLUTINACIÓN INDIRECTA E INMUNOFLUORESCENCIA INDIRECTA PARA DETERMINAR LA PREVALENCIA DE Toxoplasma gondii EN OVINOS - Huerta O., Sandra (2012)
The objective of this study was to measure the degree of concordance between the Indirect hemaglutination (HAI) and Indirect immunofluorescence (IFI) tests for Toxoplasma gondii detection in sheep. Atotal of 310 sera were collected from ewes of different ages at Fundo SantaMaría, district ofNuñoa, province ofMelgar, Puno. TheKappa (K) value was 24%, showing that the degree of association between both techniques was of a regular type. TheMcNemar test showed significative differences between both tests, so one cannot replace the other. The seroprevalence for T. gondii was 50.3 ± 5.6% through HAI test and 88.1 ± 3.5%through IFI test. Seroprevalence in animals <1, 1-2, 2-3, and >3 years of age was 23.2, 33.3, 52.1, and 58.7% through HAI test and 72.0, 90.0, 91.2, and 90.5% respectively through IFI test.